Accuracy of fully automated oscillometric central aortic blood pressure measurement techniques. Issue 2 (February 2020) - Gotzmann, Michael; Hogeweg, Maximilian; Seibert, Felix S.; Rohn, Benjamin Johannes; Bergbauer, Martin; Babel, Nina; Bauer, Frederic; Mügge, Andreas; Westhoff, Timm H.
Abstract : Background: Central aortic blood pressure (cBP) is a valuable predictor of cardiovascular risk. The lack of fully automated measurement devices impeded an implementation in daily clinical practice so far. The present study compares two novel automated oscillometric devices with invasively measured cBP. Methods: From March 2017 to March 2018, we enrolled consecutive patients undergoing elective coronary angiography to this cross-sectional study. Noninvasive assessment of cBP was performed by the SphygmoCor XCEL device and the Mobil-O-Graph NG device simultaneously to invasive measurement. Results: Our study included 502 patients (228 women, 274 men) with a mean age of 67.9 ± 11.6 years. The noninvasive measurement of cBP was successful in 498 patients (99%) with SphygmoCor XCEL device and in 441 patients (88%) with Mobil-O-Graph NG device ( P = 0.451). Measurements of both devices revealed a high correlation to invasively measured systolic (SphygmoCor R 2 0.864, P < 0.001; Mobil-O-Graph R 2 0.763, P < 0.001) and diastolic (SphygmoCor R 2 0.772, P < 0.001; Mobil-O-Graph R 2 0.618, P < 0.001) cBP. Both devices slightly underestimated systolic and overestimated diastolic central blood pressure: biases were −5.0 ± 7.7/0.5 ± 6.2 mmHg with SphygmoCor XCEL and −6.0 ± 10.4/3.6 ± 8.3 mmHg with Mobil-O-Graph NG device. Correlations ( R 2 ) were higher and biases were lower with the SphygmoCor device ( P < 0.001 each). Conclusion: The present study is the largest validation study of noninvasive cBP measurement techniques so far and shows that two current automated oscillometric monitors are able to assess cBP with acceptable accuracy. Automated oscillometric devices may facilitate the implementation of cBP in daily clinical practice. Abstract : Supplemental Digital Content is available in the text